Cross-Sector Collaboration In Improving Adolescent Reproductive Health In Garut Regency - Husnul Khotimah; Rostiena Pasciana (MUWAZAH : jurnal kajian gender, 2025)
Garut Regency faces serious problems related to the high rate of sexual violence against adolescents which indicates the need for comprehensive reproductive health treatment. This study aims to analyze the effectiveness of cross-sector collaboration in improving adolescent reproductive health through the synergy of the Garut Branch of the Indonesian Women's Coalition with the Garut Regency Family Planning Population Control Office. The research method uses a qualitative approach with a triangulation method which is assisted in analyzing using Nvivo software. This research identifies five dimensions of collaboration, namely cooperation, flexibility, responsibility, compromise, and communication. The results of the study show that collaboration is effective through the implementation of educational programs in the form of socialization, victim assistance, and sexual violence prevention campaigns. However, there are still obstacles such as social stigma in society, limited resources, and less interactive methods of delivering material. This study recommends the need for a more adolescent-friendly approach with the strengthening of interactive discussions and continuous evaluation to maximize the long-term impact on improving adolescent health in Garut Regency.